The Impact of Entry and Merger on the Price of Mobile Telecommunications Services - Georges Vivien Houngbonon (International Telecommunications Society (ITS), 2015)
According to static models of industrial organization, a rise in competition decreases prices. In this paper, I test whether this conclusion can be reversed in the mobile telecommunications markets where dynamic e ciency e ects might be signi cant. The empirical test relies on the change in the intensity of competition introduced by the entry of the fourth mobile operator in France and the merger between the third and the fourth mobile operators in Austria. Using a hedonic price model and a double-di erence matching identi cation strategy, I nd that the entry in the French market has raised the unit price of mobile data services by 4 dollars per Gigabyte; contrary to the merger in the Austrian market which lowers the unit price of mobile data by 6 dollars per Gigabyte. These results suggest that the dynamic e ciency e ects actually outweigh the static ones in the mobile telecommunications industry. Therefore, a merger from four to three mobile operators may be welfare enhancing.
Keywords: D43; L11; L13; 330; Dynamic Efficieny Effects; Ex-post Merger Evaluation; Nolinear Pricing; Mobile Telecommunications